Pathological outcomes of eyelid tumors (Annals of Medical Research, 2023)
Aim: To evaluate and compare the pathological outcomes, demographic and clinical features of benign and malignant tumors of the eyelid.Materials and Methods: The records of patients who were operated on for eyelid tumors in the oculoplastic surgery unit of our clinic were retrospectively reviewed. The age and sex of the patient, the location and laterality of the tumor, the histopathological diagnosis of the lesion, and whether it was benign or malignant were recorded.Results: A total of 251 patients who were operated on for eyelid tumors and underwent histopathological examination were included in the study. Histopathological results showed benign eyelid tumors in 230 patients (91.6%) and malignant eyelid tumors in 21 patients (8.4%). The age of the patients in the malignant eyelid tumors group was significantly higher than in the benign eyelid tumors group (p
Keywords: Basal cell carcinoma; Intradermal nevus; Sebaceous gland carcinoma; Squamous cell carcinoma